Videogrammetry application for stereo vision Bio-Production Harvester. - Wan Ismail, Wan Ishak; Ismail, Napsiah; Sulaiman, Md. Nasir; Mohamed Shariff, Abd Rashid; Razali, Mohd Hudzari (2011)
This study discusses the application of Videogrammetry technique and to define it capability for applying into bio-production arm in real cocoa plant environment. The testing was performed under laboratory control environment and dummy target point also was established to collect the actual data. The result was divided on two-application category. It is to determine the system capability to generate 3-axes coordinate (3D) target point form robot base and the accuracy of the robot arm to grab the target using mouse click method. The developed Graphical User Interface (GUI) successfully generate 3D of the targeted fruits and sent the electrical signal thru interface card for moving the robot arm and grabbing the selected target automatically.